Women and the conquest of California, 1542-1840 : codes of silence - Bouvier, Virginia Marie, 1958- (Book collections on Project MUSE., 2001)
"This is the hidden story of the missionization of California, showing what it was like for women to live and work on that frontier - and how race, religion, age, and ethnicity shaped female experiences. Virginia Bouvier explores the suppression of women's experiences and cultural resistance to domination, and reveals the many codes of silence regarding the use of force at the missions, the treatment of women, indigenous ceremonies, sexuality, and dreams."--Jacket.